2001
DOI: 10.1177/1358836x0100600305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cilostazol on resting ankle pressures and exercise-induced ischemia in patients with intermittent claudication

Abstract: Abstract:During exercise, patients with intermittent claudication (IC) have decreased limb arterial blood pressure that recovers during rest. A novel method for assessing dynamic recovery of function is measurement of the hemodynamic response after exercise. Cilostazol (Pletal  ), a new agent for the treatment of IC, increases walking distance and may decrease ischemic burden. The objective of this study was to assess the effect of cilostazol versus placebo on hemodynamic measurements after exercise-induced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 24 publications
2
21
1
3
Order By: Relevance
“…In dose-ranging trials, cilostazol administered at 100 mg twice daily was more effective than 50 mg twice daily (161,369). Cilostazol increased ABI modestly in these studies, but the hemodynamic effect could not account for the improvement in claudication (337,338,370,371). A meta-analysis of these trials indicated that cilostazol also improved walking ability and health-related quality of life (372).…”
Section: Medical and Pharmacologicalmentioning
confidence: 95%
“…In dose-ranging trials, cilostazol administered at 100 mg twice daily was more effective than 50 mg twice daily (161,369). Cilostazol increased ABI modestly in these studies, but the hemodynamic effect could not account for the improvement in claudication (337,338,370,371). A meta-analysis of these trials indicated that cilostazol also improved walking ability and health-related quality of life (372).…”
Section: Medical and Pharmacologicalmentioning
confidence: 95%
“…Cilostazol improves maximal walking distance by 40% to 60% after 12 to 24 weeks of therapy (56 -60). Cilostazol increases ABI modestly, but the hemodynamic effect cannot account for the improvement in claudication (56,57,59,61). A meta-analysis indicates that cilostazol also improves walking ability and health-related quality of life (62).…”
Section: The Usefulness Of Unsupervised Exercise Programs Is Not Wellmentioning
confidence: 94%
“…In dose-ranging trials, cilostazol administered at 100 mg twice daily was more effective than 50 mg twice daily (161,369). Cilostazol increased ABI modestly in these studies, but the hemodynamic effect could not account for the improvement in claudication (337,338,370,371). A meta-analysis of these trials indicated that cilostazol also improved walking ability and health-related quality of life (372).…”
Section: Medical and Pharmacologicalmentioning
confidence: 92%